Integrative and Complementary Practices as a possibility of mental health care (Research, Society and Development, 2021)
This theoretical essay aims to reflect on Integrative and Complementary Practices (ICP) as a possibility of mental health care. Therefore, data on current mental health are presented, the ICP are defined and their relevance in the context of mental health is discussed. It is noticed that, over the last decades, there has been an increase in the prevalence of mental health problems in the Brazilian population and this scenario has worsened in light of the Covid-19 pandemic. In view of this, it is urgent to think about mental health care strategies in order to reduce symptoms and increase well-being. In this sense, the ICP are defended as a source of care and a possibility to improve the quality of life. It is concluded that aromatherapy, homeopathy, anthroposophic medicine, chinese medicine and acupuncture, medicinal plants and herbal medicine, social thermalism or crenotherapy and yoga have positive results in the mental health of those who practice them, such as a reduction in symptoms, improved sleep and increased well-being.